Mesoamerican plazas arenas of community and power - Tsukamoto, Kenichiro 1973-; Inomata, Takeshi 1961- (University of Arizona Press, 2014)
"This is the first book to examine the roles of plazas in ancient Mesoamerica. It argues persuasively that physical interactions among people in communal events were not the outcomes of political machinations held behind the scenes, but were the actual political processes through which people created, negotiated, and subverted social realities"--
Description based on print version record
Keywords: Maya architecture -- Mexico; Maya architecture -- Central America; Indian architecture -- Mexico; Indian architecture -- Central America; Plazas -- Mexico; Plazas -- Central America; Mexiko